2002
DOI: 10.1038/sj.onc.1205416
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Snail expression with histological grade and lymph node status in breast carcinomas

Abstract: Snail is a zinc ®nger transcription factor that triggers the epithelial-mesenchymal transition (EMT) by directly repressing E-cadherin expression. Snail is required for mesoderm and neural crest formation during embryonic development and has recently been implicated in the EMT associated with tumour progression. In a series of human breast carcinomas, we have analysed the expression of Snail and that of molecules of the Ecadherin/catenin complexes. We have also correlated these data with the pathological featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
405
7
13

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 516 publications
(455 citation statements)
references
References 26 publications
30
405
7
13
Order By: Relevance
“…The E-cadherin promoter is frequently repressed by specific transcriptional repressors, including Snail1 (previously Snail), Snail2 (previously Slug), SIP1, dEF1, Twist and E12/E47, and by subsequent promoter hypermethylation [13,14]. Consistent with this observation, some of these repressors have been found expressed specifically at the invasive front of human invasive hepatocellular and breast carcinoma [15,16]. The expression of these repressors seems to be highly regulated by pathways, including canonical Wnt signaling, TGF-b (see below), FGF, EGF, Stat3 and nuclear factor k-B (NFk-B) signaling [17][18][19]).…”
Section: Changes In Cell-cell and Cell-matrix Adhesionmentioning
confidence: 62%
“…The E-cadherin promoter is frequently repressed by specific transcriptional repressors, including Snail1 (previously Snail), Snail2 (previously Slug), SIP1, dEF1, Twist and E12/E47, and by subsequent promoter hypermethylation [13,14]. Consistent with this observation, some of these repressors have been found expressed specifically at the invasive front of human invasive hepatocellular and breast carcinoma [15,16]. The expression of these repressors seems to be highly regulated by pathways, including canonical Wnt signaling, TGF-b (see below), FGF, EGF, Stat3 and nuclear factor k-B (NFk-B) signaling [17][18][19]).…”
Section: Changes In Cell-cell and Cell-matrix Adhesionmentioning
confidence: 62%
“…Significantly, Snail expression is associated to the downregulation of E-cadherin in many different carcinoma and melanoma cell lines (revised in Peinado et al, 2004a), and its expression in primary tumours has been associated to the invasive regions of squamous, breast and hepatocellular carcinomas (Cano et al, 2000;Blanco et al, 2002;Sugimachi et al, 2003). These observations, together with the ability of Snail to induce a full EMT and tumorigenic and invasive properties when expressed in epithelial cells (Cano et al, 2000;Peinado et al, 2004b), support a main role for Snail in induction of invasiveness.…”
Section: Discussionmentioning
confidence: 84%
“…Snail expression has been detected in increasing number of different human carcinoma and melanoma cell lines (reviewed in Peinado et al, 2004a). More importantly, Snail is expressed at the invasive front of epidermoid carcinomas (Cano et al, 2000) and has been associated to the lymph node status and/or invasiveness of ductal breast carcinomas and hepatocarcinomas (Blanco et al, 2002;Sugimachi et al, 2003) and to local recurrence of breast tumours (Moody et al, 2005). In addition, Snail expression has been shown to confer resistance to cell death mediated by several factors and chemotherapeutic agents (Kajita et al, 2004;Vega et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have also implicated Snail not only in E-cadherin repression but also in the acceleration of cancer invasion in various carcinomas (Batlle et al, 2000;Yokoyama et al, 2001). Blanco et al (2002) have reported that Snail expression correlated with histological grade and lymph node status in breast carcinomas, which was demonstrated by the in situ hybridisation technique. Sugimachi et al (2003) reported in a study using real-time RT -PCR that Snail mRNA levels independently correlated with capsular invasion in HCC tissues.…”
Section: Discussionmentioning
confidence: 95%